الكفاءة اللوجستية في شركة هيبروك للنقل البحري - بن عيسى, محمد جيلالي مكي (My University, 2024)
Logistics is one of the most critical activities of an organization due to its significant importance and its interaction with various organizational functions. Maritime logistics, in particular, is a prominent activity, as more than 80% of international trade shipments are transported by sea. Accordingly, this study aimed to analyze the various dimensions that affect the efficiency and performance of logistics and maritime transport in the company hyproc. The study focused on understanding the concept of logistics and how to measure its effectiveness and performance, in addition to the role of maritime transport and the impact of balancing between maritime contracts on logistical operations. The study reached several important conclusions. First, there is a positive relationship between the efficiency of logistical and administrative systems and the improvement of company performance. Improving administrative systems leads to better logistics, while enhancing logistics reduces operational costs and increases profits and customer satisfaction. Second, maritime transport plays a crucial role in improving the effectiveness of the supply chain, which enhances the company's ability to compete in the global market. Third, balancing between maritime contracts helps organize operations and clearly define responsibilities, leading to improved logistical efficiency.
Keywords: Keywords: Logistics, Shipping, Chartering, Hyproc Shipping Company.